Soluble Endoglin as a Potential Biomarker of Nonalcoholic Steatohepatitis (NASH) Development, Participating in Aggravation of NASH-Related Changes in Mouse Liver - Igreja Sá, Ivone Cristina; Tripska, Katarina; Hroch, Milos; Hyspler, Radomir; Ticha, Alena; Lastuvkova, Hana; Schreiberova, Jolana; Dolezelova, Eva; Eissazadeh, Samira; Vitverova, Barbora; Najmanova, Iveta; Vasinova, Martina; et al. (International journal of molecular sciences, 2020)
Nonalcoholic steatohepatitis (NASH) is characterized by hepatic steatosis with inflammation and fibrosis. Membrane endoglin (Eng) expression is shown to participate in fibrosis, and plasma concentrations of soluble endoglin (sEng) are increased in patients with hypercholesterolemia and type 2 diabetes mellitus. We hypothesize that NASH increases both hepatic Eng expression and sEng in blood and that high levels of sEng modulate cholesterol and bile acid (BA) metabolism and affect NASH progression. Three-month-old transgenic male mice overexpressing human sEng and their wild type littermates are fed for six months with either a high-saturated fat, high-fructose high-cholesterol (FFC) diet or a chow diet. Evaluation of NASH, Liquid chromatography-mass spectrometry (LC/MS) analysis of BA, hepatic expression of Eng, inflammation, fibrosis markers, enzymes and transporters involved in hepatic cholesterol and BA metabolism are assessed using Real-Time Quantitative Reverse Transcription Polymerase Chain reaction (qRT-PCR) and Western blot. The FFC diet significantly increases mouse sEng levels and increases hepatic expression of Eng. High levels of human sEng results in increased hepatic deposition of cholesterol due to reduced conversion into BA, as well as redirects the metabolism of triglycerides (TAG) to its accumulation in the liver, via reduced TAG elimination by β-oxidation combined with reduced hepatic efflux. We propose that sEng might be a biomarker of NASH development, and the presence of high levels of sEng might support NASH aggravation by impairing the essential defensive mechanism protecting NASH liver against excessive TAG and cholesterol accumulation, suggesting the importance of high sEng levels in patients prone to develop NASH.
Keywords: aspartátaminotransferasy; játra; Oxidative Stress; Cholesterol; Triglycerides; Alkaline Phosphatase; oxidační stres; Humans; endoglin; cholesterol; alkalická fosfatasa; Non-alcoholic Fatty Liver Disease; Aspartate Aminotransferases; jaterní cirhóza; Endoglin; bile production; Diet, High-Fat; FFC diet; Models, Biological; rozpustnost; Inflammation; lidé; fruktosa; Biomarkers; zvířata; Liver Cirrhosis; myši; zánět; Mice; NASH; triglyceridy; biologické markery; Liver; nealkoholová steatóza jater; biologické modely; Solubility; bile acids; dieta s vysokým obsahem tuků; Animals; Fructose; Disease Models, Animal; modely nemocí na zvířatech